How do drivers behave during indecision zone maneuvers?. (November 2016) - Xiong, Huimin; Narayanaswamy, Prabha; Bao, Shan; Flannagan, Carol; Sayer, James
Highlights: The study examined drivers' behavior during yellow signal indication maneuvers through a driving simulator study. Explored the impact of drivers' age, distraction, pedal conditions, and time to stop line on drivers' decision making of stopping or not at a yellow signal indication. Discovered distracted drivers' insensitive behavior from the significant interaction effect between time to stop line and distraction conditions. Abstract: Yellow signal indications at intersections are well-known to be a contributor to traffic crashes. This study examined drivers' behavior during yellow signal indication (i.e., indecision zone) maneuvers. Data from a driving simulator study was used, which included drivers' performance data when they encountered a yellow signal indication at intersections under different secondary-task conditions. This study calculated drivers' likelihood to go through a yellow signal indication and examined factors that are related to drivers' decision making on intersection traversing. The results showed that drivers' decision on stopping or not at a yellow signal indication was associated with different variables including age, distraction, pedal conditions, and time to stop line. Distracted drivers' insensitive behavior was also captured from the significant interaction effect between time to stop line and distraction conditions, which implied that intersection related crash risk may increase when drivers were distracted.